Reed, J.D. virgil’s gaze: Nation and poetry in the aeneid - Casanueva, Loreto (Revista Chilena de Literatura, 2010)
Reed, J. D. Virgil’s Gaze: Nation and Poetry in the Aeneid. Princeton: Princeton University Press, 2007. 240 pp.